Family interrelation factors and their role in family health violation in women with different levels of behavioral addiction - Савіна, Майя Василівна (ScienceRise: Medical Science, 2016)
Aim. To study conditions of family interrelation components (levels) and their role in development of family health violence in women with different levels of behavioral addiction (BA). Contingent and methods. 371 married couple (MC), asking for help against the family relationship violation, and in 321 of which manifestations of BA in women were found, were examined using clinical, psychiatric, and psycho diagnostic methods. 50 relatively harmonious MC were examined as a reference group. Results. BA, that was determined in women with family health violation moderate severity, became a way of emotional stress leveling, which occurred due to the lack of a sense of psychological support from the family, and reduced its severity level, inducing, however, a feeling of family anxiety and guilt for the situation. In contrast, women with normal addictive behavior have negative psycho-emotional frustration to realize themselves in their families, creating high level of marital and parent-child conflict without guilt or anxiety feelings because of the situation. The given results show, that the disintegrative combination of psychological properties, as well as cognitive helpless, avoiding addictive and dependent pseudo-compensatory types of behavior became the patthoplastic BA factor in women with family health violation, which formed as pathological way of psycho-emotional stress relief due to their family interrelations deformation. In the meanwhile, destructive and congruent type of combination of personality traits and cognitive uncritical, destructive conflict, and emotional-maladaptive behavioral types, pathognomonic for couples with violations of family relationship, in which women did not have addictive problems, stipulated the other ways of pathological response to the pathogenic family situation, being realized within the family, increasing the level of family stress of marital relationship degradation. Conclusion. The obtained data will be used as a base for development of the system of psychological correction and preventive support of family health in case of BA in women